9.2: A Wide‐view High Resolution 3D Display Using Real‐time Rendering Relating to Viewer Position. Issue 1 (1st July 2013) - Yang, Yingbao; Higashi, Amane; Uehara, Toshinori; Kasai, Taiki; Koito, Takeo
Abstract : Abstract: We have developed a wide‐view glass‐less 3D display using head‐tracking technology. In the head‐tracking system, the viewer's positions are captured by a real‐time camera and dedicated software and the 3D image is displayed with real‐time rendering relating to the viewer's positions. 3D crosstalk has been suppressed a low level by using an interesting multi‐pixel rendering method. 3D resolution above 170ppi has been achieved by adopting a high resolution LTPS LCD.